Evaluating dialogic communication of pesantren in East Java, Indonesia: building public relationships via instagram - Mohammad Luthfi,; Tengku Siti Aisha Tengku Mohd Azzman Shariffadeen,; Bambang Setyo Utomo,; Diah Rukmini,; Ryan Maulana Husen, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Instagram posts by pesantren are very high but replies and reactions to followers' comments are still very low, as an indicator that communication between pesantren and their public is not a two-way dialogue. This study aims to evaluate dialogic communication of pesantren in East Java, Indonesia in building public relationships via Instagram. A quantitative approach with content analysis methods is used to measure dialogic communication of pesantren on Instagram with four principles, namely the information of interest to public, the generation of return visits, the conservation of visitors and the dialogic loop. The sample was determined using purposive sampling by identifying and verifying official Instagram accounts of pesantren that had a minimum of 15 posts on June and 15 posts on July 2023. Data analysis used frequency distribution to exmine the frequency of posts. Results indicated that most of pesantren have implemented dialogic communications in building public relationships on Instagram optimally. The principle of information of interest to publics and the principle of generation of return visits are most commonly used with a very high category. The principle of conservation of visitors is low category and the principle of dialogic loop is very low category implemented. The implication of this study can provide the theoretical contribution and strategic implication on implementation the dialogic communication to build public relationships through Instagram. With a lack of study done in this area, the novelty of this study is in extending understanding on the use of dialogic communication of pesantren, especially in East Java, in building public relationships on Instagram.